PEDAGOGIK ANAK BERKEBUTUHAN KHUSUS - Mahyatun, Baiq; Suryadi, Lalu Erpan (Universitas Hamzanwadi, 2022)
Pedagogy is the science or art of being a teacher, pedagogy also refers to the proper use of teaching strategies. The learning of children with special needs requires a separate pattern that is different from learning for normal children. This is due to the existence of separate disorders that differ from one another. Students who go to school have many learning difficulties, because they generally have developmental barriers physically, emotionally, intelligence and creativity. One of the efforts for classroom teachers is to seek a form of learning intervention to overcome various kinds of disorders and the needs of their students. Teacher-interventions are mixed in such a way that they can be applied in learning and guidance on inappropriate behavior (PSS). By applying operant conditioning , and directed to a positive psychopedagogical perspective, a learning program that utilizes the Competency-Based Curriculum (KBK) is drawn up. Learning Model by utilizing Competency-Based Curriculum is one solution to overcome teacher-class difficulties in the preparation, implementation, and evaluation of individualized learning outcomes (Individualized Educational Programs). The final result is behavioral improvement that is programmed in stages through